Folic acid in low birthweight infants - Kendall, A. C. (1974)
A double-blind randomized trial of 50 μg folic acid or placebo given from 2 weeks to 6 months to 130 infants of birthweight less than 2·5 kg has been conducted. While only 62 of the babies completed the 6-month follow-up, no significant difference was found between either group in respect of changes in weight, haemoglobin, serum folate, red cell folate, or evidence of infection. It is concluded that infants in this series were receiving adequate amounts of folic acid in their normal diet and did not require supplements.